The Creation Process of a Local Museum (Cadernos de Sociomuseologia, 2009)
The present text holds as its main goal the advance of a number of reflections around the potentialities and problems of local museums taken as development instruments. Secondarily, it also intends to provide support to all those who, in one way or another, have faced the issue of creating a local museum. This support is intended not as a manual of the “the museum made easy” kind, but, instead, as the pointing to some pertinent issues and unavoidable options that, if not taken into account, will come to challenge the form and substance of the future organisation.